The Use of Cannabinoids to Treat Insomnia - Kutniauskaitė, V.; Šegždaitė, G.; Žilionytė, G.; Pajėdienė, E. (Neurologijos seminarai, 2024)
Insomnia is a sleep disorder characterized by difficulty falling asleep or maintaining sleep after waking up. With the increasing pace of life and high levels of stress, there is a rising number of individuals reporting sleep disturbances. Recently, there has been a growing interest in various cannabis preparations, particularly in cannabinoids derived from Cannabis sativa plants, for the treatment of insomnia. Delta-tetrahydrocannabinol (THC) and cannabidiol (CBD) are commonly used to treat insomnia. Both of these substances have shown potential in improving sleep quality and have historically been used to induce sleep. Despite their widespread use, there is still a lack of reliable research to prove their effectiveness. Nevertheless, cannabinoids remain frequently used substances in the management of sleep disorders. While THC and CBD may enhance the sleep quality by reducing nighttime awakenings, shortening sleep onset latency, and increasing the total sleep time, their efficacy in treating insomnia lacks scientific validation. Additionally, there are safety concerns associated with cannabinoids, including potential negative impacts on the sleep quality, risk of abuse or dependence, and the development of tolerance with long-term use. This article provides a comprehensive review of literature concerning the effects and safety of cannabinoids on sleep and sleep-wake rhythms, as well as their potential benefits in treating insomnia and other sleep disorders.